Recent Advances on the Recognition of Important Processes in Project Progress Management - Hongyan, Dui (Recent Patents on Computer Science, 2019)
Background: Comparing with the actual progress of the project and the expected target in a project management, the processes are generally inadequate due to the overall market situation and internal factors. If the progress and quality of the project cannot meet the requirements, then the processes need to be adjusted to improve the project efficiency. In the related patents of project progress management, they seldom consider the recognition of important processes. Methods: In this paper, based on Bayesian Network (BN), a new method for project progress management is provided by systematic modeling methods, reasoning methods and identification methods of importance processes. Results: Based on the importance analysis of process nodes and BN reasoning, the key processes of the project progress and the important influencing nodes of the process are identified. Conclusion: According to the results of process importance analysis, the allocation object can be got when adding the resources of the project. These are helpful to improve the operational efficiency of the project progress management and provide effective methods to identify important processes.
Keywords: operational efficiency